Portrait of Italian Cardio-Oncology: Results of a Nationwide Associazione Nazionale Medici Cardiologi Ospedalieri (ANMCO) Survey - Canale, Maria Laura; Turazza, Fabio; Lestuzzi, Chiara; Parrini, Iris; Camerini, Andrea; Russo, Giulia; Colivicchi, Furio; Gabrielli, Domenico; Gulizia, Michele Massimo; Oliva, Stefano; Tarantini, Luigi; Maurea, Nicola; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Cardio-Oncology achieved a pivotal role in the scientific scenario but real world data on its clinical impact are still limited. Methods: A questionnaire was sent out to all cardio-oncology services across Italy (n = 120). The questionnaire was made up of 28 questions divided in four blocks: A) General informations on hospital and service; B) Cardio-Oncology inner organization and relationships with out-of-hospital cardiologists and general practitioners; C) Educational needs and referral guidelines; D) Activity. Results: Ninety-six out of 120 (80%) completed the questionnaire; 9.4% were cancer centers while 90.6% were general hospitals. A cardio-oncology team was present in 56% of the cancer centers and in 20% only of general hospitals and a cardio-oncology pathway was active in 55% of cancer centers and in just 14% of general hospitals. Relationships with out-of-hospital cardiologists and general practitioners were lacking. Guidelines of reference were ESC and ANMCO/AIOM. Patients receiving anthracyclines chemotherapy underwent a schedule monitoring by means of echocardiography in 58% of cases. Routine use of cardiac damage biomarkers was overall low, ranging from 22% to 33% while the use of global longitudinal strain reached 44%. Conclusions: Italian Cardio-Oncology resulted in a chiaroscuro situation but with a growing influence on clinical practice. Clinicians want to undergo a specific training but cardio-oncology teams are still scarce and the application of dedicated paths is poor.